Measurement of the parity-violating asymmetry parameter $\alpha_b$ and the helicity amplitudes for the decay $\Lambda_b^0\to J/\psi+\Lambda^0$ with the ATLAS detector - ATLAS collaboration (2898 authors) (2014)
A measurement of the parity-violating decay asymmetry parameter, alpha_b, and the helicity amplitudes for the decay Lambda_b->J/psi(mu mu)+Lambda(p pi) is reported. The analysis is based on 1400 Lambda_b and anti-Lambda_b baryons selected in 4.6/fb of proton-proton collision data with a center-of-mass energy of 7 TeV recorded by the ATLAS experiment at the LHC. By combining the Lambda_b and anti-Lambda_b samples under the assumption of CP conservation, the value of alpha_b is measured to be 0.30+/-0.16(stat)+/-0.06(syst). This measurement provides a test of theoretical models based on perturbative QCD or heavy-quark effective theory.